Extending the Reading Performance of Low-Level Readers Through the Use of a Diagnostic Assessment Tool in Explicit Strategic Reading Instruction - Indah Welasasih Ludji (Faculty of Humanities, Universitas Jenderal Soedirman, 2020)
Explicit instruction of reading strategies has often been recommended to develop L2 or EFL learners with poor reading performance. This paper aims to examine how effective the approach is when it is combined with a diagnostic assessment tool, both on participants’ reading performance at literal and inferential levels, and participants’ attitudes towards reading. The experimental study involved two groups of 9 grade students in West Manggarai, East Nusa Tenggara who were identified as low-level readers. The findings reveal that while both control and experimental groups made significant progress in their reading performance, the experimental group yielded larger effect size than the control group. It is concluded that the use of diagnostic assessment tool was proven to be instrumental in extending the participants’ reading performance. Classroom implications and suggestions for future research are provided based on the aforementioned findings.